Catalytic Effects of the Typical Alkali Metal on Gaseous Products Distribution and Char Structure During Co-pyrolysis of Low Rank Coal and Lignocellulosic Biomass. (May 2017) - Wu, Zhiqiang; Yang, Wang Cai; Chen, Lin; Meng, Haiyu; zhao, Jun; Wang, Shuzhong
Abstract: In order to investigate the influencing mechanism of alkalis on gaseous products distribution and char structure during co-pyrolysis of low rank coal and lignocellulosic biomass, carboxymethylcellulose sodium (CMC) was selected as the typical organic sodium salt. Gaseous products distribution was explored in a drop tube furnace from 800 – 1000 o C under various CMC mass ratio, surface morphology of co-pyrolysis char was examined via scanning electron microscopy technology and fractal dimension analysis, and microcrystalline structure was evaluated using Raman spectra and peak deconvolution. The results indicated that the addition of CMC promoted the yields of H2 and CO, and the yield of CO2 was improved due to the content of carboxylate radical in CMC. Quantitative information on co-pyrolysis char surface morphology was obtained from fractal analysis on the SEM images. The fractal dimension of co-pyrolysis char was in range 1.61 to 1.78 and higher than that of coal char, which meant the uniformity of the co-pyrolysis char was promoted by CMC. Peak fitting analysis on the Raman spectra illustrated that the value of AD /AAll and AD /AG increased with the mass ratio of CMC, indicated that CMC improved the ordering of char structure. This paper provides an insight on the effects of organic sodium salt on products evolution during co-pyrolysis of coal and biomass.